CONTRIBUIÇÕES DA MÚSICA REGIONAL NA CONSTRUÇÃO DA IDENTIDADE HISTÓRICO-CULTURAL DO MATO GROSSO DO SUL – SENDAS EM CANÇÕES DE GERALDO ROCA - IAN RARI NOGUEIRA FARIA (2024)
This research aims to discuss the construction of the historical and cultural identity of Mato Grosso do Sul through the regionalism present in the work of Geraldo Roca. In this sense, the dissertation is based on the dialogue between approaches of Cultural Studies and aspects of historical and philosophical reflections and will discuss concepts of identity, culture and border, through four compositions by this artist: “Trem do Pantanal”, “Polka outra vez”, “Uma pra estrada” and “Mochileira”. Thus, based on the documentary and bibliographical survey, the aim will be to understand the historical context of the creation of the state, the festivals of Mato Grosso do Sul and Roca's musical compositions. After all, it can be said that the region is rich in cultural and historical diversity — in addition to finding in the work of Geraldo Roca a vivid expression of its regionalism. Thus, through his artistic production, the composer offers a vision deeply rooted in the region's identity, exploring elements ranging from the natural landscape to the traditions and experiences of the people of Mato Grosso do Sul. Thus, through Geraldo Roca's songs, one of the objectives was to capture the essence of Mato Grosso do Sul, highlighting aspects of the local culture – such as folklore, the unique landscapes of the Pantanal and the Cerrado, as well as the historical nuances that shaped the identity of the place – contributing to the preservation and celebration of the region's cultural identity. Thus, this research, by exploring themes such as the relationship between man and nature, social conflicts and collective memory, seeks, through Geraldo Roca's work, not only to highlight, but also to actively contribute to the construction and preservation of the historical and cultural identity of Mato Grosso do Sul.